Approach guide for patient orientation for adherence to pharmacotherapy in heart failure (Research, Society and Development, 2021)
Objective: to develop a quick and easy consultation tool to standardize the conduct of different members of the care team for pharmaceutical guidance and promotion of adherence to pharmacotherapy in heart failure (HF). Method: experimental development study that consisted of bringing together the authors' experience and recommendations published in technical and scientific publications for the development of an instrument to support the pharmaceutical guidance approach and promotion of adherence of patients with HF. Development: the Guide was organized in the form of a table that lists the type of approach according to the patients' responses to the Morisky-Green Test (TMG) items, considering the intentional and unintentional factors that interfere with the adherence behavior, reconciling the approach of the 4 items of the TMG to the approach of 16 reasons for non-adherence by Culig. A third set of factors was also added, which are those related to medications. Conclusion: the Guide was developed and applied, proving to be a useful tool to streamline and standardize the conduct during the pharmacotherapeutic follow-up to patients with HF, contributing to better results in interventions to promote adherence.